Strategi dalam Meningkatkan dan Mempertahankan Kualitas Konten pada Program Affiliate Tiktok Shop (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study explores the strategies applied by TikTok Shop affiliates in improving and maintaining content quality amid digital competition. The study uses a qualitative descriptive method through interviews with two active affiliates in West Kalimantan. SWOT analysis is used to identify internal and external factors affecting content performance. The data analysis technique uses qualitative data analysis with stages of data reduction, data presentation, and drawing conclusions. The main results show that consistency in content creation, building audience trust, adapting to algorithms, and leveraging visual trends play a crucial role in content effectiveness. This study emphasizes the importance of content credibility and audience engagement in supporting sustainable affiliate success.